Leadership Management Style and Teacher Performance: A Descriptive Study at the Baitul Aziz Educational Foundation in Bandung - Rahmadianti (Institut Agama Islam Persis Bandung, 2024)
This study analyzes the leadership management style on teacher performance. Theoretically, leadership style is very important in developing good management in an institution. This study aims to explore the leadership management style on teacher performance at the Baitul Aziz Education Foundation in Bandung. The research method used in this study is a qualitative approach with a descriptive method. Data collection techniques used in this study are observation and interviews. Informants in this study used a purposive technique, namely the parties involved in leadership management at the Baitul Aziz Education Foundation in Bandung. The findings in this study are that the leadership management style on teacher performance at the Baitul Aziz Education Foundation in Bandung has criteria in advancing the foundation, namely the head of the institution and the teachers support every job done by the head of the foundation for the common good and the progress of the foundation, not on the basis of personal interests and deliberation in making a decision with the head of the institution and the teachers. In addition, it is able to create a pleasant family atmosphere both with the heads of the institution and with the teachers. Another thing is that in the performance structure, always provide clear work instructions or tasks and provide rewards or awards for every institutional leader and teachers who perform well and evaluate institutional leaders and teachers who do not perform well.